Pengaruh Bauran Pemasaran terhadap Kepuasan Pasien yang diperoleh dari Tingkat Kunjungan Pasien ke Rumah Sakit: Literature Review - Safi’i, Akhmad; Sulistiadi, Wahyu (UI Scholars Hub, 2020)
Efforts to satisfy consumer needs are carried out by every company with various strategies and methods with the hope that consumers will be satisfied and will make repeat purchases. If a consumer has turned into a loyal customer because his satisfaction is fulfilled, then the consumer will not switch to other similar company products or services. In the context of a hospital as well, people will selectively choose a hospital that they consider satisfied with hospital services and the impact on loyalty obtained from increased patient visits. This article aims to determine the effect of the marketing mix on patient satisfaction obtained from the level of hospital patient visits. This study uses a literature review method through the Google Schoolar database source. Search literature from the Google Scholar database source using the keywords